‘Nuestra patria La Habana’: Reading the 1762 British Occupation of the City - Guadalupe García (Centre de Recherches sur les Mondes Américains, 2011)
This essay explores the 1762 British occupation of Havana. It argues that the military crisis served as a catalyst for the emergence of a discursive space where racial hierarchies were momentarily suspended as residents attempted to make sense of the unfolding events. 1762 thus functions as a window into the military transformations that the city experienced and their effect on race relations in colonial Havana. The descriptions of events and heroes can be understood within the larger process of collective identity-formation that was part of the racially inclusive independista discourses of the nineteenth century.